PEMBINAAN LITERASI MEDIA DAN PELATIHAN JURNALISTIK PADA ANAK-ANAK DI LPKA KELAS II KOTA BATAM - Sholihul Abidin; Angel Purwanti (ASOSIASI IDEBAHASA KEPRI, 2021)
Batam City Class II Child Prison is a place where children who commit criminal acts are sanctioned by imprisonment or are referred to as assisted residents. A place like this is definitely far from adequate educational facilities. Starting from the limited number of coaches in the institution to the difficulty of children receiving education heoretically. In carrying out the Tridharma of Higher Education, the Communication Studies Study Program sees that the existing situation needs attention. The academics need to feel like they are involved in the prison's assisted children to provide guidance on media literacy, especially in the field of journalism and writing news that focuses on becoming a citizen journalism or citizen journalism. In addition to being able to add insights and education for assisted residents at the Class II Child Prison in Batam City, this guidance also contributes to the world of journalism practitioners. Citizen journalism or citizen journalism is an alternative solution to limited resources and events beyond the reach of the mass media. Community involvement to participate in documenting an event that occurred in this environment can add complete information about important events to be known by the wider community. The material for writing news is carried out by introducing journalism to the community of Binaa first. In the first meeting, those who are interested in participating in the activity will be selected as many as 10-20 assisted residents. Furthermore, they will receive intensive news writing training for 3 to 4 meetings. As well as making sure they can write with news or just information properly and correctly according to journalistic principles. This coaching activity will be carried out around September-October 2017.